Behavior-Based Pricing and Delay Commitment in Congestion-Prone Systems - Fang, Lei; Ouyang, Ying; Wang, Zhongbin; Zhan, Dongyuan (Production and Operations Management, 2026)
Recent years have witnessed the widespread use of data to recognize repeat and new consumers to offer them different prices, that is, behavior-based pricing (BBP). While extensive research has explored the market impacts of BBP, most studies overlook the congestion effects arising from increased demand. This study addresses this gap by investigating the impact of BBP in congestion-prone systems, such as food delivery, with a particular focus on how delay commitment strategies influence both firms and consumers. Employing a two-period game-theoretic duopoly model integrated with a queueing system, where service qualities can be dynamically adjusted in each period, our analysis shows that BBP consistently intensifies firm competition, leaving firms worse off while simultaneously benefiting consumers. To enable BBP as a viable equilibrium, we propose a delay commitment strategy. Our findings show that while BBP intensifies price competition, it further alleviates service competition when combined with delay commitment. Notably, when capacity costs are high, the moderating effect on service competition becomes dominant, thereby offsetting the adverse impact of BBP on firms and ultimately leading to higher profits. From a long-term perspective, we further confirm that adopting delay commitment constitutes a Pareto-dominant equilibrium for both firms, irrespective of whether BBP is implemented. We further show that BBP continues to mitigate service competition even under partial coverage and may help increase market coverage. Moreover, when firms differ in their capacity costs, our results show that BBP can enhance social welfare by alleviating the negative externalities associated with congestion, termed the load-balancing effect. In summary, our research highlights the potential drawbacks of BBP for firms in service systems, but suggests that adopting a delay commitment strategy can revitalize BBP.